THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDES, AND TRAINING OF FOOD HANDLERS WITH GOOD FOOD PRODUCTION METHODS IN FOOD HOUSEHOLD INDUSTRIES IN KOTA BARU SUB-DISTRICT, JAMBI CITY - Andy Amir ,; Andi Subandi, (International Journal Of Health Science, 2023)
Background : In this world, food safety management was poor. In addition it has increasing every year and it would be food poisoning. A way to good food production for the household industry (CPPB-IRT) really need to be considered, because they can be dangerous for consumers. The aim this studi to analyze knowledge, attitude, and trainning with CPPB-IRT. The purpose of the study was to determine whether there was a relationship between knowledge, attitude, training of food handlers and CPPB in the home industry industri.Method : The type of this stiudy is quantitative with cross sectional design. Sample in this research are 60 respondents were selected using the Total Sampling method. The dependent variable is CPPB and independent variable are knowledge, attitude, and training participation in good and correct food production methods. Data was collected by means of interviews. Analysis using Chi Square.Research result : The results of this study indicate that 44 out of 60 (73.3%) respondents with bad CPPB and 16 (26.7%) respondents with good CPPB. There are significancy relation between knowledge (P-value=0,038; POR=4,1) and attitude (P- value=0,015; POR=5,2) with CPPB. There is no relation with training with CPPB.Conclusion: There are significancy relation between knowledge and attitude with CPBB. There should be training to increase the knowledge of employees that have an impact on a positive attitude for CPBB accomplished